Numerical analysis of ice accretion on an airfoil: A case study - Lucas Farabello; Ana Scarabino; Federico Bacchi (Revista Facultad de Ingeniería Universidad de Antioquia)
The accumulation of ice on aircraft surfaces is known to endanger flight safety, which has driven the study and development of various methods to prevent this issue. A frequent problem aircrafts suffer is the ice accumulation on wings when flying across clouds with supercooled droplets. The shape and size of the ice accretion depend essentially on the flying speed, air temperature, number and size of microdroplets present in the atmosphere, and the exposure time to ice formation conditions. The numerical analysis of ice accretion involves differential equations for the resolution of the air velocity field, the transport of droplets, and their icing and melting. In this work, numerical models implemented in ANSYS CFD and Fensap-Ice codes are validated against experimental results and then applied to compute the ice formation on an MS(1)-0313 airfoil, used in a SAAB 340 wings, an aircraft that suffered a lethal accident in the Argentine Patagonia on May 18th, 2011. The simulation parameters were chosen based on meteorological reports of that day and the type of clouds that were present at the time of the accident. The goal of this work is to apply Fensap-Ice to verify whether icing on the wings could have been the cause of the accident. The results of this study confirm that the hypothesis is highly probable.